Public perception of forestry practices in Malaysia - Ratnasingam, Jegatheswaran; Vacalie, Cristina; F. Sestras, Adriana; Ioras, Florin (Academic Pres,University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca, 2014)
This article endeavours to assess public perceptions about the importance of forests for young people in the age group of 21-35 years in Malaysia based on 1,503 reliably answered interviews. Overall patterns show that timber production and environment protection are very important attributes among this age group. The interviews indicated high awareness of negative environmental impacts of deforestation, with high levels of concern over higher temperatures, air pollution and loss of clean water sources. Large-scale deforestation (e.g., for industrial oil palm plantations) and political interference appeared to be more context-dependent, with most respondents considering it to have on overall negative impact on sustainable forestry in Malaysia. Increasing information accessibility, awareness and experience in the forest of the young people could ultimately result in positive processes.